First mtgenome sequences from three genera and phylogenetic relationships of the family Apidae based on mtgenome sequences (Hymenoptera: Apoidea). Issue 3 (4th March 2021) - Wen, Zhong-Quan; Li, Ting-Jing; Wang, Hua-Chuan; Yuan, Huan; Chen, Bin
Abstract: In this study, we report the complete mitochondrial genomes (mtgenome) of Thyreus decorus, Ceratina okinawana and Amegilla calceifera, which are the first time of mtgenome report also for the genera Thyreus, Ceratina and Amegilla in the family Apidae. They contain 15, 237, 15, 207, and 17, 728 bp, with AT content of 84.97%, 79.30%, and 84.63%, respectively. Each mtgenome includes 13 protein-coding genes (PCGs), 22 transfer RNA (tRNAs), two ribosomal RNA (16S and 12S rRNA) and an AT-rich control region (CR). The phylogenetic relationships of 45 species in the family were constructed using Bayesian Inference based on concatenated nucleotide sequences of 13 PCGs. Our study suggests that the subfamily Apinae is a paraphyletic group, with the genus Eucera claded into the subfamily Xylocopinae and the genera Amegilla and Thyreus into the subfamily Nomadinae. In Apinae, the genera Melipona and Bombus are significantly sister group, and the genus Apis is the sister group with Melipona + Bombus .